Transcriptome Reprogramming of CD11b+ Bone Marrow Cells by Pancreatic Cancer Extracellular Vesicles - Maia, Joana; Otake, Andreia Hanada; Poças, Juliana; Carvalho, Ana Sofia; Beck, Hans Christian; Magalhães, Ana; Matthiesen, Rune; Strano Moraes, Maria Carolina; Costa-Silva, Bruno (Frontiers in Cell and Developmental Biology, 2020)
Pancreatic cancers (PC) are highly metastatic with poor prognosis, mainly due to delayed detection. We previously showed that PC-derived extracellular vesicles (EVs) act on macrophages residing in the liver, eliciting extracellular matrix remodelling in this organ and marked hepatic accumulation of CD11b+ bone marrow (BM) cells, which support PC liver metastasis. We here show that PC-EVs also bind to CD11b+ BM cells and induce the expansion of this cell population. Transcriptomic characterization of these cells shows that PC-EVs upregulate IgG and IgA genes, which have been linked to the presence of monocytes/macrophages in tumor microenvironments. We also report here the transcription downregulation of genes linked to monocytes/macrophages activation, trafficking and expression of inflammatory molecules. Together, these results show for the first time the existence of a PC-BM communication axis mediated by EVs with a potential role in PC tumor microenvironments.